2008
DOI: 10.1044/1092-4388(2008/069)
|View full text |Cite
|
Sign up to set email alerts
|

Self-Esteem, Shyness, and Sociability in Adolescents With Specific Language Impairment (SLI)

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
85
1
10

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(106 citation statements)
references
References 63 publications
(112 reference statements)
10
85
1
10
Order By: Relevance
“…Again, this data is consistent with findings on adolescents with SLI (Botting & Conti-Ramsden, 2000;Wadman et al, 2008). Nevertheless, their problems are sufficiently severe to be recognized by teachers and parents as well as themselves suggesting that they impact on many aspects of their everyday lives.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Again, this data is consistent with findings on adolescents with SLI (Botting & Conti-Ramsden, 2000;Wadman et al, 2008). Nevertheless, their problems are sufficiently severe to be recognized by teachers and parents as well as themselves suggesting that they impact on many aspects of their everyday lives.…”
Section: Discussionsupporting
confidence: 81%
“…In a study of friendships in 16-year old students with SLI, 60% reported having good quality friendships (Durkin & Conti-Ramsden, 2007). Furthermore, their problems rarely fall within the clinical range of the disorder (Botting SOCIAL AND EMOTIONAL FUNCTIONING IN ADOLESCENCE 7 & Conti-Ramsden, 2000;Redmond & Rice, 1998;Wadman et al, 2008). Recent longitudinal studies of well-being and quality of life (Carroll & Dockrell, 2010;Dockrell, Lindsay, Palikara & Cullen, 2007;Palikara, Lindsay & Dockrell, 2009) report more positive long term outcomes than earlier studies (Clegg et al, 2005;Howlin, Mawhood & Rutter, 2000;Mawhood, Howlin & Rutter, 2000).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Shy children speak less in conversation because they have poor language skills with a limited amount of vocabularies [17]. This is a worrying scenario because if the children do not utilise the opportunity in such social interaction, their language abilities are at risk and affect their academic learning as well as social competencies [18]. The researchers argued that shyness and poor communication skills lower the self-esteem of an individual.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The uses and gratification approach acknowledges the individual characteristics as another variable that effects the differences in user responses to the same or similar media (Stone et al, 1999). Thus, interactivity inherent to social media usage and communication may emphasize the active role of socialiability, the tendency to affiliate and to prefer being with others (Santesso et al, 2004;Wadman et al, 2008;Rai, 2011), as an individual characteristic.…”
Section: Hypotheses Of the Studymentioning
confidence: 99%